Evolving talent management patterns and challenges in Russia and Kazakhstan: Investigating employer perspective. Issue 3 (1st July 2019) - Khoreva, Violetta; Kostanek, Edyta
Abstract : Purpose: The purpose of this paper is to investigate the evolving patterns and challenges of talent management (TM) in the emerging markets of Russia and Kazakhstan from the employer perspective. Increasing the understanding of how TM is recognized from the employer perspective may better equip us to address how to effectively manage and lead the available talents in these and other emerging markets. Design/methodology/approach: The authors conducted a qualitative study comprising 50 semi-structured interviews, with 37 business leaders from Russian subsidiaries, and 13 from Kazakh subsidiaries, in all cases of Nordic Multinational enterprises (MNEs). Findings: The study supports the object approach to TM in the emerging markets of Russia and Kazakhstan. The authors reveal that the exclusive and developable talent philosophy is predominant in these emerging markets, where TM faces the challenges of fierce competition for talents and an insufficient supply, so business leaders tend to be reluctant to inform employees of their talent pool membership. The results demonstrate that MNEs do not act independently of context, thus supporting calls for consideration of the local institutional context. Originality/value: TM is still a somewhat novel idea in many emerging economies, and challenges related to managing talents are believed to be far more complex in such settings. Furthermore, to the best of authors' knowledge, no studies have investigated the notion of talent and TM conceptualization in the emerging markets from an employer perspective.